PENGARUH MODEL KOOPERATIF BERBANTUAN KARTU BERGAMBAR TERHADAP PEMAHAMAN MINYAK BUMI DI SMAN 9 PONTIANAK - Siseh Siseh; Hairida Hairida; Lukman Hadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThe background of this study were unsatisfying achievement of students and boring method. The purposes of this study were to determine whether there was a significant difference of achievement of students  taught using pictorial card assisted cooperative learning model and cooperatif learning model, to determine effect size of  pictorial card assisted cooperatif learning model. The form of this study was quasi-experimental research with nonequivalent control group design. From three of XI classes of SMAN 9 Pontianak, two sample were selected. According to cluster random sampling technique XI MIA 2 was selected as experimental class and XI MIA 1 was selected as control class. Achievment test, instrument quideline, and observation sheet were used to collect data. According to U-Mann Whitney test, probability of significant value was 0,006 which meant there was a significant difference of concept understanding between students who taught using pictorial card assisted cooperative learning model and cooperative learning model. According to calculation using glass formula, the effect size of pictorial card assisted cooperative learning model towards concept understanding was 0,71 which categorized as medium..Keywords: Cooperative, Pictorial Card, Concept Understanding